Distribution and ecological aspects of Rhodnius pallescens in Costa Rica and Nicaragua and their epidemiological implications - Zeledón, Rodrigo (2006)
In light of the Central American Initiative for the control of Chagas disease, efforts were made on the part of Costa Rican and Nicaraguan teams, working separately, to determine the present status of Rhodnius pallescens in areas close to the common border of the two countries, where the insect has appeared within the last few years. The opportunity was also used to establish whether R. prolixus, a vector present in some areas of Nicaragua, has been introduced in recent years into Costa Rica with Nicaraguan immigrants. It became evident that wild adults of R. pallescens are common visitors to houses in different towns of a wide area characterized as a humid, warm lowland, on both sides of the frontier. Up to the present, this bug has been able to colonize a small proportion of human dwellings only on the Nicaraguan side. There was strong evidence that the visitation of the adult bug to houses is related to the attraction of this species to electric lights. There were no indications of the presence of R. prolixus either in Nicaragua or in Costa Rica in this area of the Caribbean basin. Triatoma dimidiata, a widespread domestic species in both countries, was totally absent in the explored areas of Costa Rica but occasionally occurs on the Nicaraguan side. Serological surveys in children of both areas showed that transmission of Chagas disease takes place in a rather small degree in Costa Rica and more commonly in Nicaragua, indicating that R. pallescens could be a potential threat as a vector in this particular region.